Enhancing Parent-Child Relationships through Innovative Reading Strategies: A Study of Migrant Worker Families in Guangzhou - Lu, Son In (Transactions on Social Science, Education and Humanities Research, 2024)
The effects of children's books on parent-child relationships have been studied with families of migrant workers in Guangzhou, China. The study looks into the challenges of book selection and ways ineffective reading methods impact the population. In our survey during volunteer work at Guangzhou STARS Welfare libraries we noted that parents did not participate in the reading activity with their children. We later employed a mixed-method approach using both quantitative surveys (n=126) and qualitative interviews (n=5) to gather data on reading habits, book preferences and how an online library would impact them from the same people surveyed earlier. Results showed that parents preferred illustrated books (66.9%) and science books (37.1%) more than any other type, for reasons such as gaining knowledge (35%), building relationships with others (33.8%), or improving their reading skills (30.4%). To overcome these challenges identified we suggest two strategies: organizing offline activities in STARS welfare libraries; creating an online library platform on WeChat through which parents can access audiobooks, videos plus other reading resources available. The exploration of unconventional reading strategies helps to explore the bond between parent and child and at the same time nurtures a child during his early childhood which can be used in places where there are not many resources, like migrant worker families. The online library described was welcomed by those interviewed and may likely serve as a handy resource for enhancing parent-child reading experiences.